FIRST RECORD OF POPLAR LEAF TWERS, EPINOTIA ABBREVIANA (TORTICIDAE: Lepidoptera) ON POPULUS SP. TREES IN IRAQ. - Ismail N.Almaroof (Mesopotamia Journal of Agriculture)
The life cycle of Epinotia abbreviana Fabi (Tortricidae : Lepidoptera) was studied and recorded for the first time in Iraq in 2006 under laboratory conditions (30.5°c and 25.5%R.H). The study showed that the mean length of incubation period, larval stages and longevity of adults, males and females, were 7.51, 19.92 and 7.37, 7.27 days respectively. The study also showed that all larval instars have the ability to tie two or more leaves together and feed on the epidermis of the tied up leaves. The study indicated that the mean number of eggs laid by a singles female were 98.70, and the egg viability 82%. The sex ratio of male to female was 1.2:1. Also it was found that this species has 5 generations per year. The average duration of each generation was 38.10 days. The toxicities of some insecticides on the second and the fifth larval stages were evaluated. These insecticides were Alphacypermethrin, Diazinon, Endosulfan and Sevin with concentrations ranged from (0.0010-0.0300) %. Alphacypermethrin showed higher toxicity effect on larvae and significantly difference from other insecticides. And Sevin toxicity has the lowest effect of the tested insecticides. Diazinon and Endosulfan had less toxicity effects on larval than Alphacypermethrin respectively.